Management effectiveness: Evaluating on recruiting process at Creative Agency, MAA Seremban branch / Sharifah Nazira Syed Idros Alkaff - Syed Idros Alkaff, Sharifah Nazira (Faculty of Business and Management, 2007)
This research is conducted in order to find out the most effective activities that the agency do in order to maintain their effectiveness and efficiency of the management. Besides that, it also to ensure all the existing activities is still relevant in the future time. It is the job of the Chief Consultant to ensure that the recruiting processes are run smoothly and effectively in order to maintain their consultant comfortable to do the business with the agency. The objectives of this study are to describe the level of effectiveness of the activities done in Creative Agency. Besides that, it also to describe the activities of managing recruiting in Creative Agency. Other than that, it to determine the level of effectiveness in managing recruiting in Creative Agency besides to identify the factors that influences the Managing Recruiting in Creative Agency. The last objective is to describe the recommendations of management effectiveness in Creative Agency. The sampling used in this research is simple random sampling under probability sampling. Descriptive research design is used that was carrying out among the consultant of Creative Agency in Seremban. The target population for this research is he consultant in Creative Agency that will be selected randomly from the total population of 63 consultants in Creative Agency. Data that used in this research is primary data that consist personal interviews and questionnaires. From the finding, the result shown that most of the consultant on Creative Agency have uncertain effectiveness with the management, and certain factors should be reviewed by the management of Creative Agency such as motivation, training, management, beneflts / incentives and also communications.